The Comparison of a Thematic versus Regional Approach to Teaching a World Geography Course. Issue 4 (3rd July 2016) - Korson, Cadey; Kusek, Weronika
Abstract : The benefits of a regional or thematic approach to the study and presentation of world geography have long been debated. The goal to not to reimagine these debates or to promote one approach over another; the aim is to explore how world geography courses are currently being taught in American universities. By polling and sharing information about course structures, topics, and forms of evaluation, an open dialogue between instructors that will improve teaching strategies and student comprehension is encouraged.